Corruptionary diksyonaryo ng mga salitang korapsyon sa Pilipinas = a dictionary of Filipino corruption words - Ilagan, Bonifacio P.; Tuazon, Bobby M.; Dela Torre, Fidel Llagas (Anvil Publishing, Inc., 2010)
Filipino dictionary of corrupt and political terms.